Do African Children Have an Equal Chance? : A Human Opportunity Report for Sub-Saharan Africa - Dabalen, Andrew; Narayan, Ambar; Saavedra-Chanduvi, Jaime; Suarez, Alejandro Hoyos; Abras, Ana; Tiwari, Sailesh (Washington, DC: World Bank, 2014)
This study explores the changing opportunities for children in Africa. While the definition of opportunities can be subjective and depend on the societal context, this report focuses on efforts to build future human capital, directly (through education and health investments) and indirectly (through complementary infrastructure such as safe water, adequate sanitation, electricity, and so on). It follows the practice of earlier studies conducted for the Latin America and the Caribbean (LAC) region (Barros et al. 2009, 2012) where opportunities are basic goods and services that constitute investments in children. Although several opportunities are relevant at different stages of an individual s life, our focus on children s access to education, health services, safe water, and adequate nutrition is due to the well-known fact that an individual s chance of success in life is deeply influenced by access to these goods and services early in life. Children s access to these basic services improves the likelihood of a child being able to maximize his/her human potential and pursue a life of dignity.